Critical features and challenges associated with imaging in patients undergoing cancer immunotherapy. (December 2017) - Solinas, Cinzia; Porcu, Michele; Hlavata, Zuzana; De Silva, Pushpamali; Puzzoni, Marco; Willard-Gallo, Karen; Scartozzi, Mario; Saba, Luca
Abstract: Manipulating an individual's immune system through immune checkpoint blockade is revolutionizing the paradigms of cancer treatment. Peculiar patterns and kinetics of response have been observed with these new drugs, rendering the assessment of tumor burden particularly challenging in cancer immunotherapy. The mechanisms of action for immune checkpoint blockade, based upon engagement of the adaptive immune system, can generate unusual response patterns, including pseudoprogression, hyperprogression, atypical and delayed responses. In patients treated with immune checkpoint blockade and radiotherapy, a reduction in tumor burden at metastatic sites distant from the irradiation field (abscopal effect) has been observed, with synergistic systemic immune effects provoked by this combination. New toxicities have also been observed, due to excessive immune activity in several organs, including lung, colon, liver and endocrine glands. Efforts to standardize assessment of cancer immunotherapy responses include novel consensus guidelines derived by modifying World Health Organization (WHO) and Response Evaluation Criteria In Solid Tumors (RECIST) criteria. The aim of this review is to evaluate imaging techniques currently used routinely in the clinic and those being used as investigational tools in immunotherapy clinical trials.